Performance prediction of prefabricated vertical drain in soft soil using finite element method - Teh, Zhi Huan (2015)
Soft soil ground improvement method by using preloading with prefabricated vertical drain (PVD) had successfully applied in many soft ground construction projects. Due to the complexity of today’s construction work, finite element method could assist designers to model very complex subsoil and structural elements. In this study, finite element analysis is performed to verify the effectiveness of modelling of PVD in subsoil using computer software, Plaxis V8. The field settlement data were collected at two particular locations and were analysed using Asaoka’s (1978) method to estimate the ultimate settlement and back-calculated the coefficient of horizontal consolidation for these two particular location. Thereafter, by using backcalculated coefficient of horizontal consolidation, finite element analyses were performed to predict the time rate settlement and compared against field settlement results. From the time rate settlement curves generated by FEM, the ultimate settlements were predicted using Asaoka’s (1978) method. It was found that the predicted time rate settlement by FEM shows reasonable agreement with the actual field settlement result. The ultimate settlement predicted from FEM is slightly lower compared to actual field settlement monitoring result, but the degree of consolidation settlement achieved were higher. In term of time required to achieve 90% consolidation settlement after surcharge, FEM shows slightly advancement compared to actual field settlement monitored. However, the advancement is only within 5% which is in good agreement with the actual field monitored reading